Exploration of Occupational Accident Risk Factors Causing Worker Disability in the Coconut Flour Industry - Nelwin Nelwin; Netty Ino Ischak; Laksmyn Kadir (GLOBAL HEALTH SCIENCE GROUP, 2026)
Occupational accidents in the coconut flour industry in Gorontalo Regency remain a serious threat to workers, with an increasing incidence rate and a high risk of causing permanent disability. This study aims to analyze the risk factors for work-related accidents leading to disability among workers in the coconut flour industry of Gorontalo Regency. This research is a qualitative study utilizing a case study approach. Data collection was conducted through in-depth interviews, field observations, and documentation. The informants consisted of workers with disabilities resulting from occupational accidents, the person in charge of the Occupational Health and Safety Management System (OHSMS), and OHS practitioners. Data analysis was performed using the Miles and Huberman model. The results indicate that accidents leading to disability are dominated by the sheller unit. These incidents are triggered by the interaction between unsafe actions and unsafe conditions. Behavioral factors include low OHS knowledge, rushed work attitudes to meet production targets, and non-compliance with the use of standardized Personal Protective Equipment (PPE). These conditions are exacerbated by substandard physical work environments, characterized by high room temperatures (32.3°C–33.7°C) and dim lighting (132–176 Lux), which significantly reduce worker concentration. Furthermore, the suboptimal implementation of OHSMS policies and management supervision increases the risk of fatalities.